Seleção de linhagens de feijão de ciclo precoce, arquitetura ereta, alta produtividade e cozimento rápido - Santos, Guilherme Godoy dos (2014)
The objectives of this study were to evaluate whether advanced common bean lines differ in phenological, morphological, grain yield and cooking quality characters; to study the linear correlations between these characters; and to select superior lines for these characters for use in breeding programs. For this purpose, 14 common bean lines of trial Use and Cultivation South -Brazilian Bean (VCU - SB) were growing in normal rainy 2012/2013 and in dry season 2013 in Santa Maria, Rio Grande do Sul, Brazil. Data were subjected to analysis of individual and joint variance, using the F test at 5 % probability. If the effect of line and control was significant, the stratification of averages was performed by the Scott-Knott test at 5 % probability. Interaction line x growing season significant was observed for the characters: number of days from emergence to flowering, reproductive period, cycle, lodging, stay green, number of lateral branches, number of pods per plant, number of grains per plant, number of grains per pod, weight of 100 grains, grain yield, grain length and width. The line and control evaluated differed significantly among the characters: number of days from emergence to flowering, cycle, number of nodes on main stem, width and thickness of grains, grain brightness and time of cooking, allowing you to select improved lines for these characters. Positive linear correlation of high magnitude was observed between grain yield and number of pods per plant (r = 0.632) and weight of 100 grains (r = 0.942), while the grain yield and the number of days from emergence to flowering (r = -0.857) and the cycle (r = -0.677) had high negative linear correlation. The LP 09-40 line and BRS Valente control have the lower note of lodging in the two growing seasons, allowing the use of these blocks of crosses to obtain lines with erect architecture. The CNFP 10794 and DF 06-17 lines may be used as parents in hybrid combinations for presenting high yield and reduced cooking time and high yield and early cycle, respectively.